Pola Penerapan Pembelajaran Pendidikan Karakter Religius di Madrasah Tsanawiyah Ma’arif Nu Sutojayan - M. Nofian Hamdani (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
Education basically aims to shape the character of students. The expected goals in education are stated in Law Number 20 of 2003 concerning the National Education System in article 3, the contents of which are "National education functions to develop and shape the character and civilization of a dignified nation in order to make the nation's life more intelligent, aimed at developing the potential of students so that to become a human being who believes and is devoted to God Almighty, has noble character, is healthy, knowledgeable, capable, creative, independent, and becomes a democratic and responsible citizen. This research was conducted to determine the pattern of implementation of religious character education learning at Madrasah Tsanawiyah Ma'arif NU Sutojayan. This research uses a qualitative research approach with a case study type. The methods used to collect data are interviews, observation and documentation. Then the researcher used source triangulation and technique triangulation. This research produces several conclusions that the learning pattern for religious character education at the Madrasah Tsanawiyah Ma'rif NU Sutojayan is through the habit of performing religious services at a certain time, as well as in terms of tolerance for social objects. There are students who are excessive in their appearance of decorating themselves, wearing gold bracelets that are not supposed to be worn when school time. There are also students who are not fluent in connecting Indonesian sentences neatly, especially when asking questions to the teacher during class time, which results in ridicule from their friends.The teacher's efforts to maintain an attitude of tolerance towards students' awareness of students' awareness of accepting differences in conditions by providing understanding, advice, motivation and direction as a group which is encouraged by providing exemplary examples shows good relations in social life between teachers without distinction.